Variasi Pupuk Cair Limbah Tempe Terhadap Pertumbuhan Tanaman Sawi Caisim (Brassica juncea L.) Dengan Hidroponik Sistem Wick - Yunita Panca Putri; Inka Dahlianah; Jumingin Jumingin; Suhal Nur Rahma; Bianto Bianto (Universitas PGRI Palembang, 2022)
Utilization of tempe liquid waste from the boiling and soaking process can be made as liquid fertilizer. Liquid fertilizer contains beneficial bacteria to fertilize soil and plants. The role of beneficial bacteria in this liquid fertilizer is to bind nitrogen (N), phosphorus (P), potassium (K) and other elements for plant needs, so as to increase plant productivity. The purpose of this research was to examine variations in the application of liquid fertilizer from tempe waste to growth of caisim mustard plants (Brassica juncea L) with wick hydroponic system. This study despised a completely randomized with 5 treatment 4 nameli with. is P0 (control/no nutrition ), P1 (150 ml liquid fertilizer by tempe waste /liter of water), P2 (200 ml liquid fertilizer by tempe waste /liter of water), P3 (250 ml liquid fertilizer by tempe waste /liter of water), P4 (300 ml liquid fertilizer by tempe waste /liter of water). And four replicates. The data is analyzed by partial print analysis (ANSIRA). The parameters observed are the height of the plant, how much of leaves, the weigh . The results showed that giving nutrition of liquid fertilizer by tempe waste have a significant effect on plant height, number of leaves and wet height from caisim mustard plants (Brassica juncea L). The highest treatment was obtained at the dose 200 ml for all parameters with an average of height of plant was 16,5 cm, successively the average number of leaves was 8,25 strands, and a wet weight of plant was 2,85 grams.